Pengaruh Good Corporate Governance, Moralitas Individu, dan Personal Culture Terhadap Pencegahan Kecurangan Pada Lembaga Perkreditan Desa (LPD) Se - Kecamatan Tejakulaa - Komang Riska Pratiwi; Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of good corporate governance, individual morality, and personal culture on fraud prevention in LPD Se – Tejakula District. This research is quantitative research. The sample used is as many as 95 with a sampling technique that is saturated sampling. In this study, the data used were primary data, namely a questionnaire which was measured using SPSS. The results of this study indicate that (1) good corporate governance has a positive and significant effect on fraud prevention, (2) individual morality has a positive and significant effect on fraud prevention, (3) personal culture has a positive effect on fraud prevention